Pengaruh Work Life Balance, Job Satisfaction dan Burnout Terhadap Turnover Intention pada Generasi Z Di PT. Rocket Chicken DIY - Yanto, Feri; Bandri, Fitri Susilowati (Akmenika: Jurnal Akuntansi dan Manajemen, 2024)
This research aims to determine the influence of work life balance, job satisfaction, and burnout on turnover intention. The respondents in this research were employees of Rocket Chicken Companny Generation Z in the Special Region of Yogyakarta.This research was conducted from February to Mart 2024. This research is quantitative research with a total of 100 respondents with a sampling technique using non-probability sampling with purposive sampling type. Data collection uses a questionnaire distributed. The analysis technique uses multiple linear aggression with the help of SPSS Version 23 for Windows.The research results concluded that work life balance had a negative and significant effect on turnover intention. Job satisfaction has a negative and significant effect on turnover intention. Burnoout has a positive and significant effect on turnover intention. Work life balance, job satisfaction, and burnout simultaneously have a significant effect on turnover intention.This research is interesting to carry out because there is an opinion that Generation Z is a generation that does not have a long-term commitment to the company